Transcatheter Aortic Valve Implantation in Alkaptonuria-Аssociated Severe Aortic Stenosis: A 2.5-Year Follow-Up Case Report and Literature Review - Spas Kitov; Maria-Florance Kitova; George Goranov; Krasimir Kraev; Maria Kraeva; Lyudmila Kitova (Life)
Introduction: Alkaptonuria is an autosomal-recessive disorder affecting the metabolism of tyrosine and phenylalanine which results in accumulation of homogentisic acid in connective tissues. The joints are most commonly affected, while the most common cardiac damage is aortic valve stenosis. The treatment focuses on reducing the symptoms. Aortic stenosis in alkaptonuria is treated with surgical aortic valve replacement; however, transcatheter aortic valve implantation procedures are increasing in number with excellent outcomes. Case presentation: We report a case of a 67-year-old female with chronic back pain and large-joint arthralgia, who was recently diagnosed with alkaptonuria. She reported a long-known heart murmur and intermittent dark-brown staining of her underwear since childhood. Bilateral dark-brown pigmentation of the sclera and both ear cartilages were visualised. ECG confirmed atrial fibrillation and left ventricular hypertrophy. Cardiac ultrasonography showed severe aortic stenosis, reduced global longitudinal strain and preserved ejection fraction. According to the latest recommendations, the choice between surgical and transcatheter intervention must be based upon careful evaluation of clinical, anatomical and procedural factors by the Heart Team, weighing the risks and benefits of each approach for an individual patient. The advantages and disadvantages of both procedures were explained to the patient. It was emphasised that the genetic disease present has no etiopathogenetic definitive treatment and the pigment may continue to deposit on the biological valve (in transcatheter aortic valve implantation) and less likely on the mechanical valve prosthesis (in Surgical Aortic Valve Replacement), highlighting the fact that in the literature worldwide, there are only single reports of ochronosis and severe aortic stenosis. At this stage of knowledge, it is difficult to give the patient clear guarantees when choosing a methodology for performing a valve correction. Along with the standard therapy the patient underwent transcatheter aortic valve implantation with Boston Scientific prosthesis with a very good post-procedural outcome. Conclusions: There is scarce information on transcatheter aortic valve implantation success rate in patients with alkaptonuria. In the population, transcatheter aortic valve implantation outcome is generally good; however, the individual success in alkaptonuria patients depends on the severity of their heart valve damage and overall health.